Parachute Method: A Novel Method to Retrieve a Stuck Degloved Finger - Periasamy, Madhu; Asokan, Kumanan; Mohan, Monusha; Muthukumar, Vamseedharan; Venkatramani, Hari; Sabapathy, S. Raja (Indian Journal of Plastic Surgery, 2022)
An entrapped finger is a relatively uncommon domestic injury. When the finger gets stuck proximal to the proximal interphalangeal joint, the resultant distal edema and inappropriate attempts at retrieval can result in circumferential degloving of the skin and injury to the neurovascular structures. We report a technique that can be used in such circumstances. Strategically placed skin sutures are used to get the skin through the constricting ring, and retrieval is aided by a cut finger glove that wraps the finger and can be lubricated. This non-cutting technique is named as the parachute technique since the withdrawn skin sutures look like the strings of the parachute. This technique is valuable when the finger gets stuck in an idli plate, a common South Indian kitchen utensil, where there is difficulty of access to cutting equipment and where inappropriate attempts at retrieval can result in skin injury making further attempts more difficult.
Keywords: idli plate; finger; domestic injury